Synthesis of alpha-amino phosphonates by three component condensation of carbonyl compound, amine, and dialkyl phosphite using Yttria-zirconia based Lewis acid catalyst - Ramalingam, S.; Kumar, Pradeep (Catalysis Letters, 2008)
An efficient Yttria-zirconia Lewis acid catalyzed one-pot synthesis of alpha-amino phosphonates by three component coupling reaction of a carbonyl compound amine and dialkyl phosphates is described in good to high yield.
Keywords: alpha-amino phosphonates; three component coupling; Yttria-zirconia based Lewis acid catalyst